Pengembangan Komik Penanganan Sampah Rumah Tangga Berbasis Karakter untuk Masyarakat di Perumahan Nasional Griya Aur Duri Indah Kota Jambi: Comic Development of Household Waste Management Based on Character for the Community in Perumahan Nasional Griya Aur Duri Indah Jambi City - Wella Yosvita Sari; Aprizal Lukman; Afreni Hamidah (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2018)
A person's character influences his habits. This can be seen from the habits of the people in the Griya Aur Duri Indah Housing in the City of Jambi in handling household waste; some people do not know how to handle household waste properly. This development research aims to produce products in the form of character-based household waste management comics for the community in the Griya Aur Duri Indah Housing in Jambi City, and to asses its feasibility and community responses to the comics produced. The development employs the Borg and Gall development model. This development research resulted in a product in the form of a character-based household waste management comic for the community at the Griya Aur Duri Indah Housing in Jambi City. Media validator considers the product in the valid category, whereas material validator considered the product as very valid. The results of trials in small groups and large group trials obtained values ​​with very good categories. Based on the results it can be concluded that the character-based household waste management comics for the community in the Griya Aur Duri Indah Housing in Jambi City can foster good community character related to waste management and can be implemented to the community.